2012
DOI: 10.5114/aoms.2012.29535
|View full text |Cite
|
Sign up to set email alerts
|

State of the art paper Routine infant immunization with the 7- and 13-valent pneumococcal conjugate vaccines: current perspective on reduced-dosage regimens

Abstract: A b s t r a c tThe 7 and 13-valent pneumococcal conjugate vaccines are mostly used in routine infant immunizations to prevent the development of pneumococcal disease. Currently, the dosing schedule approved and recommended for PCV7 and PCV13 in infants is 3 primary doses followed by a booster dose in the second year of life. However, a number of countries use a 2-dose only primary series with a booster dose in the second year of life. This review is aimed at providing the reader with a broad perspective on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…O'Brien et al found that it causes around 11% of all deaths in children aged 1-59 months worldwide [21]. According to a survey conducted in Poland between 2003 and 2004, the highest incidence for IPD in children was observed among those 0-2 years old [22]. For the reasons mentioned above, a pneumococcal vaccine was heavily promoted in the media at the time of the survey, not only by pharmaceutical companies but also by recognizable health experts, which might have influenced the parents' decision.…”
Section: Parents' Choice Regarding Self-paid Vaccinesmentioning
confidence: 97%
“…O'Brien et al found that it causes around 11% of all deaths in children aged 1-59 months worldwide [21]. According to a survey conducted in Poland between 2003 and 2004, the highest incidence for IPD in children was observed among those 0-2 years old [22]. For the reasons mentioned above, a pneumococcal vaccine was heavily promoted in the media at the time of the survey, not only by pharmaceutical companies but also by recognizable health experts, which might have influenced the parents' decision.…”
Section: Parents' Choice Regarding Self-paid Vaccinesmentioning
confidence: 97%
“…In 2016, a study evaluated the safety and immunogenicity of different doses of P2-VP8-P ( 8 ) subunit vaccine. 528 infants were enrolled in this experiment, and the experimental group's anti-P2-VP8 IgG serum showed significantly higher antigen responses to P ( 4 ), P ( 6 ), and P ( 8 ) compared to the control group ( 63 ). At present, there are inactivated RV vaccines (IRVs) based on the G1P ( 8 ) strain, which have shown good immune and protective effects in animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the independent variation of G-type and P-type, a dual naming system is usually used to determine the strain type ( 12 ). Among them, VP7 (G1-G4, G9, and G12) binds to VP4 (P ( 4 ), P ( 6 ), and P ( 8 ), causing most humans worldwide to be infected with RV and leading to diarrhea ( 13 ). In recent years, the main serotypes of RV prevalent in China include G1, G2, G3, G4, and G9 ( 14 ).…”
Section: Relevant Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both reviews note the variation by serotype in the immune response after the first 2 versus the first 3 doses. 8,9 For most serotypes there are only modest reductions in the immune response after 2 doses; however, for serotypes 6B and 23F the diminution in immune responses is more significant. The World Health Organization estimated that an antibody concentration of 0.35 mg/mL for all PCVassociated serotypes correlates with clinical efficacy against IPDs related to that specific vaccine serotype.…”
mentioning
confidence: 95%